LEGALITAS TALAK DI LUAR PENGADILAN DALAM PERSPEKTIF HUKUM DI INDONESIA - Masri (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
Divorces outside the courts are frequently performed by Muslims in Indonesia, and are notlegally binding. This study aims to analyze the status of divorces outside the courts according topositive law, dualism of legality, and the analysis of the maqashid sharia (the principle ofIslamic law) of divorce in court. In the national legal system, divorce for Muslims is regulatedby Law Number 1 of 1974 concerning Marriage, as amended by Law Number 16 of 2019, and isemphasized in the Compilation of Islamic Law, which stipulates that divorce can only beobtained in court. This study uses a descriptive analytical method with a normative juridicalapproach through statutory and conceptual analysis. The results indicate that divorces issuedoutside the courts are considered valid religiously according to Islamic jurisprudence, but haveno administrative legal force and are not recognized by the state until they are decided by aReligious Court. Therefore, it is necessary to increase public legal awareness and strengthenthe role of the judiciary to ensure the protection of rights and legal certainty for the parties.